Smutty wheat in swine diets - G L Allee (Kansas Agricultural Experiment Station Research Reports, 1980)
Smutty wheat substituted for milo in diets for pigs from 20-60 pounds did not affect pig performance.; Swine Day, Manhattan, KS, November 13, 1980
Keywords: Swine day; 1980; Kansas Agricultural Experiment Station contribution; no. 81-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 388; Swine; Smutty wheat; Milo